2012
DOI: 10.1785/0120110289
|View full text |Cite
|
Sign up to set email alerts
|

The Large Chilean Historical Earthquakes of 1647, 1657, 1730, and 1751 from Contemporary Documents

Abstract: The four largest historical earthquakes of central Chile in the seventeenth and eighteenth centuries,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 14 publications
3
50
0
Order By: Relevance
“…The length and positions of rupture planes along the trench were taken from data collections of Beck et al (1998), Comte et al (1986), Comte & Pardo (1991) and Udías et al (2012). The rupture length and location for recent strong events were taken from Barrientos & Ward (1990) for the M9.6 1960 Valdivia earthquake, Delouis et al (1997) for the M7.6 1987 earthquake near Antofagasta, Ruegg et al (1996) for the M8.0 1995 Antofagasta earthquake, Pritchard & Simons (2006) for the M9.6 1960 Valdivia earthquake, Chlieh et al (2011) for the M8.4 2001 Arequipa earthquake, the rupture plane of which extends well into our area of investigation, Schurr et al (2014) for the M7.9 2007 Tocopilla earthquake, Yue et al (2014) for the M8.8 2010 Maule earthquake, Geersen et al (2015) and Schurr et al (2014) for the M8.1 2014 Iquique earthquake, and Tilmann et al (2016) for the M8.2 2015 Illapel earthquake.…”
Section: Data Preparationmentioning
confidence: 99%
“…The length and positions of rupture planes along the trench were taken from data collections of Beck et al (1998), Comte et al (1986), Comte & Pardo (1991) and Udías et al (2012). The rupture length and location for recent strong events were taken from Barrientos & Ward (1990) for the M9.6 1960 Valdivia earthquake, Delouis et al (1997) for the M7.6 1987 earthquake near Antofagasta, Ruegg et al (1996) for the M8.0 1995 Antofagasta earthquake, Pritchard & Simons (2006) for the M9.6 1960 Valdivia earthquake, Chlieh et al (2011) for the M8.4 2001 Arequipa earthquake, the rupture plane of which extends well into our area of investigation, Schurr et al (2014) for the M7.9 2007 Tocopilla earthquake, Yue et al (2014) for the M8.8 2010 Maule earthquake, Geersen et al (2015) and Schurr et al (2014) for the M8.1 2014 Iquique earthquake, and Tilmann et al (2016) for the M8.2 2015 Illapel earthquake.…”
Section: Data Preparationmentioning
confidence: 99%
“…earthquake whose magnitude is estimated to be M S 8. 5-9 (LOMNITZ 2004), and its rupture area is estimated to be extended from Coquimbo (30°S) down to the northern part (35°S) of the rupture zone of the 2010 Maule, Chile, earthquake (e.g., UDIAS et al 2012). The last significant earthquake in this region, but much smaller than the 1730 earthquake, was the M S 7.9 1943 Illapel earthquake (Centennial Catalog;ENGDAHL and VILLASEÑ OR 2002), and its source region estimated by BECK et al (1998) overlaps the rupture area of the 2015 Illapel earthquake (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The 1928 Talca earthquake in Maule Region with an estimated magnitude of M 7.6 (Beck et al 1998;Ruegg et al 2002) is far smaller than the 2010 Maule earthquake, and is not considered here. The central slip zone of the Maule earthquake ruptured in 1835 by an earthquake of M ∼ 8.2 (Udias et al 2012;NOAA 2015). The Concepción earthquake in 1751 affected a very large region from Santiago to Valdivia, and caused a large tsunami.…”
Section: Strain Accumulation Time Implied By Historical Mega-earthquamentioning
confidence: 99%
“…The Concepción earthquake in 1751 affected a very large region from Santiago to Valdivia, and caused a large tsunami. It has been suggested that it had a similar size and extent as the 2010 Maule earthquake (Udias et al 2012;Bernhardt et al 2015). Although the M ∼ 8.2 event in 1835 has possibly ruptured the central slip zone of the Maule earthquake, it is far smaller than the 2010 event (the former released only ∼1/18 of the seismic moment of the latter).…”
Section: Strain Accumulation Time Implied By Historical Mega-earthquamentioning
confidence: 99%